China in the world economy: Dynamic correlation analysis of business cycles - Jarko Fidrmuc; Ivana Bátorová (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
We analyse the business cycles in China and in selected OECD countries between 1992 and 2006. We show that, although negative correlation dominates for nearly all countries, we can also see large differences for various frequencies of cyclical developments. On the one hand, nearly all OECD countries show positive correlations of the very short-run developments that may correspond to intensive supplier linkages. On the other hand, business cycle frequencies (cycles with periods between 1.5 and 8 years) are typically negative. Nevertheless, countries facing a comparably longer history of intensive trading links tend to show also slightly higher correlations of business cycles with China.
Keywords: E32; F15; J50; 330; business cycles; synchronisation; trade; FDI; dynamic correlation; Konjunkturzusammenhang; China; OECD-Staaten